Tribological behavior of thin film coating-a review - Chandra Yadaw, Ramesh; Kumar Singh, Shailesh; Chattopadhyaya, Somanth; Kumar, Sanjeev; C. Singh, R (International Journal of Engineering and Technology, 2018)
An automotive industry sectors are facing major challenges to produce materials of high hardness, low wear rate and corrosive resistant due to international intrinsic norms. Scientist and researchers are developing new materials with different surface properties to come over the international intrinsic norms and hence, they are trying to enhance tribological behavior and increase the life of automotive parts, make the parts corrosive resistant. Therefore, it has become essential to explore the new combinations of coating materials. A tribome-chanical effect of hard metal (WC-12 % Co and Cr3C2-25 % NiCr) coating on the cast iron and steel substrate were compared. Micro hardness, porosity, microstructure, corrosion and economical factor were compared and concluded that the hardness of WC-12%Co & Cr3C2-25NiCr coated on mild steel substrate were comparatively superior but the Cr3C2-NiCr coated cast iron substrate was better over WC-12%Co because it was more economical and corrosive resistant and competitive wear characteristics and as the temperature and load are increased, the Cr3C2-NiCr shows excellent wear resistances.Â Â